2023
DOI: 10.1126/sciadv.adf5056
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic streaming enabled moderate swimming exercise reduces neurodegeneration in C. elegans

Abstract: Regular physical exercise has been shown to delay and alleviate neurodegenerative diseases. Yet, optimum physical exercise conditions that provide neuronal protection and exercise-related factors remain poorly understood. Here, we create an Acoustic Gym on a chip through the surface acoustic wave (SAW) microfluidic technology to precisely control the duration and intensity of swimming exercise of model organisms. We find that precisely dosed swimming exercise enabled by acoustic streaming decreases neuronal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…By adjusting the duration and power intensity of SAW actuation, an optimal exposure setting has been found that substantially mitigates neurodegenerations in both models. This research underscores the nuanced relationship between exercise parameters and neuroprotection in C. elegans, unveiling the acoustofluidic gym as an instrumental tool for further inquiries in this domain [141,142]. More clinically, Gai et al have contributed an innovative, automated methodology for the selection of high-quality sperm, targeting the resolution of male infertility [143,144].…”
Section: Acoustofluidic Biophysical Therapymentioning
confidence: 87%
“…By adjusting the duration and power intensity of SAW actuation, an optimal exposure setting has been found that substantially mitigates neurodegenerations in both models. This research underscores the nuanced relationship between exercise parameters and neuroprotection in C. elegans, unveiling the acoustofluidic gym as an instrumental tool for further inquiries in this domain [141,142]. More clinically, Gai et al have contributed an innovative, automated methodology for the selection of high-quality sperm, targeting the resolution of male infertility [143,144].…”
Section: Acoustofluidic Biophysical Therapymentioning
confidence: 87%